2017
DOI: 10.1027/0227-5910/a000410
|View full text |Cite
|
Sign up to set email alerts
|

Newspaper Reporting on a Cluster of Suicides in the UK

Abstract: 21Background: Media reporting may influence suicide clusters through imitation or contagion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…This came at a time when good quality reporting was essential for suicide prevention. Reporting of a possible suicide cluster began before there were more suicides than expected in the area (John et al, 2016). The presence of a higher than expected number A CONTENT ANALYSIS AND COMPARISON OF TWO PEAKS OF NEWSPAPER REPORTING DURING A SUICIDE CLUSTER TO EXAMINE IMPLICATIONS FOR IMITATION, SUGGESTION AND PREVENTION of deaths during P1 but not during P2 presents a rare opportunity to examine features of reporting for potential contagion.…”
Section: Recommendations For Responsible Reporting Of Suicides Have Bmentioning
confidence: 99%
See 1 more Smart Citation
“…This came at a time when good quality reporting was essential for suicide prevention. Reporting of a possible suicide cluster began before there were more suicides than expected in the area (John et al, 2016). The presence of a higher than expected number A CONTENT ANALYSIS AND COMPARISON OF TWO PEAKS OF NEWSPAPER REPORTING DURING A SUICIDE CLUSTER TO EXAMINE IMPLICATIONS FOR IMITATION, SUGGESTION AND PREVENTION of deaths during P1 but not during P2 presents a rare opportunity to examine features of reporting for potential contagion.…”
Section: Recommendations For Responsible Reporting Of Suicides Have Bmentioning
confidence: 99%
“…Increases in suicide deaths in young people following the release of a controversial television series was found to be concordant with the period in which social media discussions of the series were greatest (Niederkrotenthaler et al, 2019). While press coverage in this cluster preceded it s statisti al sta t (John et al,2016) the role of the media must be considered alongside other modes of transmission, such as word of mouth (Haw et al, 2013).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Several studies have attempted to assess adherence to suicide reporting guidelines across various countries and forms of media, including new media, with disappointing results (Abbott, Ramchand, Chamberlin, & Marcellino, 2017;Easson, Agarwal, Duda, & Bennett, 2014;John et al, 2016;Utterson, Daoud, & Dutta, 2017;Young, Subramanian, Miles, Hinnant, & Andsager, 2017). A recent study examining the fidelity of media reporting on Robin Williams' suicide found that 55% of articles surpassed the 80% threshold for "high fidelity" and 85% of articles applied at least 70% of the guidelines.…”
Section: Existing Guidelinesmentioning
confidence: 99%
“…Suggestions have been made to increase adherence to guidelines, including involving media organizations in the development of suicide reporting strategies to increase buy-in and increasing efficiency of disseminating recommendations to media organizations (Scherr, Arendt, & Schäfer, 2016). While more research is needed, the development of new instruments to systematically evaluate news reports could advance our knowledge in the near future (John et al, 2014(John et al, , 2016Nutt, Kidd, & Matthews, 2015).…”
Section: Existing Guidelinesmentioning
confidence: 99%
“…Previous studies have analyzed all health-related materials in general newspapers [8,12]. Others have analyzed specific sports [13,14,15,16], organic diseases [17,18,19,20,21,22,23,24] and/or psychological illness [25,26,27,28,29,30]. A similar previous study was published [18]; however, the analysis only focused on athletes’ medical information disclosed by English newspapers.…”
Section: Introductionmentioning
confidence: 99%